Micro/Nanobubbles Driven Multimodal Imaging and Theragnostics of Cancer - Xiaoting Zhang, BS, Zhifei Dai, PhD (Editorial Office of Advanced Ultrasound in Diagnosis and Therapy, 2021)
Ultrasound imaging has attracted great interest of researchers due to their application in cancer diagnosis and treatment. Ultrasound contrast agents, microbubbles and nanobubbles are widely explored as a multifunctional platform, not only carrying other contrast agents for multimodal imaging to complement the disadvantages of each imaging modality, but also carrying drug/gene for cancer theragnostic. In this article, the characteristics and differences of microbubbles and nanobubbles are briefly introduced and reviewed. Besides, the microbubbles and nanobubbles driven multimodal imaging and theragnostic of cancer are summarized.